Comparison of standard versus ultrasound guidance in radial and femoral access: a subanalysis of the randomised SURF trial. (25th November 2020) - Nguyen, P; Makris, A; Hennessy, A; Jayanti, S; Xuan, W; Juergens, C
Abstract: Background: Ultrasound (US) guidance in facilitating arterial access may reduce vascular complications and possible bleeding. There are still limited trials assessing real-time US guidance for coronary angiography. The SURF (Standard versus ultrasound-guided radial and femoral access in coronary angiography and intervention) trial showed no difference in primary outcome when the combined radial and femoral ultrasound analysis compared with standard (SD) technique, but significantly improved access efficiency and success rate. Purpose: This subanalysis compared clinical and procedural outcomes of the individual radial and femoral access with US guidance versus standard technique. Methods: Patients (n=1388) undergoing coronary angiography and percutaneous coronary intervention were randomised (1:1) into radial or femoral access, and (1:1) to SD or US guidance. The primary outcome was a composite of ACUITY (Acute Catheterisation and Urgent Intervention Triage strategY) major bleeding, MACE (death, stroke, myocardial infarction or urgent target lesion revascularisation) and vascular complications at 30 days. Secondary outcomes were access time, number of attempts, venepuncture, difficult accesses and first-pass success. Results: Compared to standard, US guidance produced no difference in composite endpoint for both radial (1.4% vs 1.2%, p=0.78) and femoral (3.1% vs 3.8%, p=0.65) accesses. ACUITY major bleeding (radial: 0.9% US vs 0.6% SD, p=0.69; femoral: 1.9% US vs 2.3% SD, p=0.69), vascular complications (radial: 0.3% US vs 0.3% SD, p=0.98; femoral: 1.3% US vs 0.9% SD, p=0.63) and MACE (radial: 0.6% US vs 0.3% SD, p=0.59; femoral: 0.9% US vs 1.2% SD, p=0.78) were similar in the US and SD approaches, respectively. However, US guidance resulted in improved procedural outcomes for both accesses. Femoral access derived the most benefit from US, with reduced mean access time (73 sec vs 97 sec, p=0.006), attempts (1.35 vs 1.84, p≤0.0001), difficult accesses (1.8% vs 6.2%, p=0.004), venepuncture (5.8% vs 12.6%, p=0.002) and improved first-pass success (77.2% vs 58.8%, p≤0.0001). For radial, US reduced attempts (1.59 vs 1.97, p=0.0007), difficult accesses (6.9% vs 12.3%, p=0.02), venepuncture (2.5% vs 5.6%, p=0.04) and improved first-pass success (69.2% vs 60.7%, p=0.02). There was no difference in radial mean access time (111 sec vs 126 sec, p=0.18). Conclusions: US guidance in radial and femoral access did not reduce primary outcome compared to standard technique. The use of US significantly improved the efficiency and success rate of arterial cannulation, with femoral access derived the most benefit. Funding Acknowledgement: Type of funding source: None